Whole proteome analysis of germinating and outgrowing Bacillus subtilis 168 - Pospíšil, Jiří; Sax, Alice; Hubálek, Martin; Krásný, Libor; Vohradský, Jiří (Proteomics, 2024)
In this study, we present a high-resolution dataset and bioinformatic analysis of the proteome of Bacillus subtilis 168 trp+ (BSB1) during germination and spore outgrowth. Samples were collected at 14 different time points (ranging from 0 to 130 min) in three biological replicates after spore inoculation into germination medium. A total of 2191 proteins were identified and categorized based on their expression kinetics. We observed four distinct clusters that were analyzed for functional categories and KEGG pathways annotations. The examination of newly synthesized proteins between successive time points revealed significant changes, particularly within the first 50 min. The dataset provides an information base that can be used for modeling purposes and inspire the design of new experiments.
Keywords: bakteriální proteiny; Proteome; Bacterial Proteins; Bacillus subtilis; Proteomics; Computational Biology; Spores, Bacterial; proteomika; výpočetní biologie; spory bakteriální; proteom